The Effect of Well-Being and Humanist Leadership Style on Performance with Work Motivation as a Mediating Variable in Employees of PT PLN (Persero)ULP West Binjai - Suhardi; Sri Rahayu (Equivalent : Journal of Economic, Accounting and Management, 2026)
This study aims to analyze the effect of well-being and humanistic leadership style on employee performance, with work motivation as a mediating variable among employees of PT PLN (Persero) ULP Binjai Barat. This research adopts a quantitative approach using a survey method. The research sample consists of 100 employees, determined using a census technique. Data were collected through questionnaires and analyzed using Partial Least Squares–Structural Equation Modeling (PLS-SEM). The results show that well-being has a positive and significant effect on employee performance and work motivation. Humanistic leadership style also has a positive and significant influence on employee performance and work motivation. However, work motivation does not have a significant effect on employee performance. In addition, work motivation does not mediate the relationship between humanistic leadership style and employee performance, nor does it mediate the relationship between well-being and employee performance. These findings indicate that employee performance is more strongly influenced directly by well-being and humanistic leadership style rather than through work motivation as a mediating variable.